Kajian Hukum Pidana Terhadap Pelaku Tindak Pidana Perdagangan Orang (Studi Putusan Nomor: 1824/Pid.Sus/2023/PN.Mdn) - simanjuntak, immanuel; Bayu Syahputra, Yoga; Ramenta Sembiring, Rio (DOKTRINA: JOURNAL OF LAW, 2025)
This study aims to describe human trafficking as a criminal offense and to examine legal protection for victims of trafficking from the perspective of positive law in Indonesia. This is a normative legal research using a statutory approach with legal materials as the primary data. Human trafficking is a serious crime that violates human values and justice, and it has developed into a transnational organized crime. The Indonesian Criminal Code includes several provisions addressing this offense, including Articles 289, 295, 296, 297, 324, and 328. Additionally, Law Number 21 of 2007 concerning the Eradication of the Criminal Act of Human Trafficking explicitly regulates the elements and imposes strict penalties on perpetrators. In Decision Number: 1824/Pid.Sus/2023/PN.Mdn, the defendant was found guilty of exploiting a child and was sentenced to six years of imprisonment and fined one hundred and twenty million rupiah. The results of this research show that legal protection for victims is regulated, yet its implementation still requires strengthening to ensure justice and the full restoration of victims' rights.